Algorithmic Fairness: The Intersection of Socio-Technological Development and the Needs of Legal Hermeneutics (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This work employs fairness as a dialogical term between law and technology. Critiquing the rigid and semantic construction of the concept, tied to a formalistic logic, fairness is reformulated as a metaphor for in fieri machine legal decision making, grounded in argumentation through principles and values in concrete cases. The study then analyses the impossibility for formal algorithms to adhere to such directives, proposing the recognition of a right to algorithmic contestability to “return” to the adopted hermeneutic framework. Finally, it explores how some stochastic systems may align with this perspective, showing “uncanny” behavioural analogies between human and machine action in legal decision making.
Keywords: Fairness; jurimetrics; legal hermeneutics; machine decision-making; behaviourism